2021
DOI: 10.1080/15732479.2021.1907601
|View full text |Cite
|
Sign up to set email alerts
|

Extensive testing on PVC sewer pipes towards identifying the factors that affect their operational lifetime

Abstract: Polyvinyl chloride (PVC) sewer pipes have operated for decades in a hostile environment, raising concern among sewer managers over the longevity of their drainage systems. Inspection data (CCTV and PanoramoV R ) reveals that severe defects have already surfaced, yet it is unknown if the material properties of PVC sewers have been affected. In order to address this issue, extensive testing (among others flexural and tensile tests, FT-IR, X-ray, viscosity measurements) was conducted on eight exhumed PVC sewer pi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…The results shown in Table (4) and Figure (5) for resistance to external blows testing indicated that the percentage of broken specimens (10%) conformed to the specification limits when calcium carbonate addition was 3, 5, and 8% while the percentage of broken specimens increased to 60 and 40% when calcium carbonate addition was 10 and 15% it did not conform to the specification and the reason is due to the heterogeneity of the polyvinyl chloride with the increasing proportion of calcium carbonate which led to such cracks as shown in Figure (6).…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…The results shown in Table (4) and Figure (5) for resistance to external blows testing indicated that the percentage of broken specimens (10%) conformed to the specification limits when calcium carbonate addition was 3, 5, and 8% while the percentage of broken specimens increased to 60 and 40% when calcium carbonate addition was 10 and 15% it did not conform to the specification and the reason is due to the heterogeneity of the polyvinyl chloride with the increasing proportion of calcium carbonate which led to such cracks as shown in Figure (6).…”
Section: Resultsmentioning
confidence: 89%
“…The plastic pipe production process goes through the stages (grafting stage, cooling, and heating stage, extrusion stage, and cutting stage) [4] . Over the past decades, Polyvinyl chloride (PVC) has become one of the dominant construction materials in urban drainage systems, as well as for drinking water and gas distribution networks, is used in many industrial products, the most important of which is that it is used in the manufacture of plastic pipes and sewage pipes where they have a long service life and is used in packing electrical wires, as well as in medical devices, blood storage bags, window blinds, paint in automobile, building construction and packaging fields [5,6,7,8,9]. And calcium carbonate is used in many fields for example in the paint industry as an aid in rubber processing as an additive in the paper industry as well as in the medical purposes, in the manufacture of chemical fertilizers, pesticides and glass and as a filler in the plastic industry, calcium carbonate improves some of the physical properties of the plastic product they make an antioxidant where it raises its stability and resistance and make it a good external appearance as well as a texture in addition they make it easy to treat and raise its fluidity and scattering, the use of calcium carbonate in the plastics industry reduces production costs because it is much cheaper than petroleum and other raw materials and calcium carbonate constitutes (80%) of all fillers used in the plastic industry of which approximately 65% are consumed from (U.PV.C) compounds with an annual consumption rate of about 6 million tons, its wide use is mainly related to presence in abundance in nature and with good purity and this in turn is reflected in the low cost of processing as it is produced in different sizes and with multiple processes that include drying, grinding and softening to a granular size ranging from 100µ to less than 5µ [10].…”
Section: Iraqi Journal Of Industrial Research (Ijoir)mentioning
confidence: 99%